Kebijakan Bebas Peredaran Uang (BPU) Dalam Mencegah Peredaran Narkotika Berdasarkan Pasal 5c Permenkumham No. 29 Tahun 2017 di Lembaga Pemasyarakatan Narkotika Kelas IIB Muara Sabak - Rahman, Juni; Abdullah, M. Zen; Fatriansyah, Fatriansyah (Legalitas: Jurnal Hukum, 2024)
Since the establishment of the Correctional Institution which was originally called a prison and State Detention Center, various regulations have been implemented regarding money control in the Correctional Institution and Detention Center. However, various efforts that have been made through the implementation of regulations and arrangements for restrictions or policies on free circulation of money in Correctional Institutions/Detention Centers are still not in accordance with the expected goals. There are still often violations that stem from the rampant circulation of cash in Correctional Institutions/Detention Centers, one of which is in the Class IIB Muara Sabak Narcotics Correctional Institution. The purpose of this study is to understand and analyze the Free Circulation of Money  policy in preventing the circulation of narcotics based on Article 5C of the Minister of Law and Human Rights Regulation No. 29 of 2017 in the Class IIB Muara Sabak Narcotics Correctional Institution.